Growth in Europe. Notes for a Policy Agenda - Pier Carlo Padoan (Credit and Capital Markets – Kredit und Kapital, 2020)
This paper discusses topics related to the growth mechanism in Europe, and specifically in the eurozone. It looks at the interaction of macroeconomic and structural aspects identifying issues where more analysis is needed in order to draw policy implications. It also looks at how developments in the governance of global system are affecting growth. Finally it looks at how political economy obstacles to a stronger growth environment and a structural agenda can be overcome by improving incentives to collective action.
Keywords: E6; F320; F330; 330; Growth; Europe; Eurozone